PENGARUH PENAMBAHAN GLISEROL TERHADAP SIFAT KEKUATAN TARIK DAN PEMANJANGAN SAAT PUTUS BIOPLASTIK DARI PATI UMBI TALAS - Rinaldi Febrianto Sinaga, Gita Minawaris Ginting, M. Hendra S Ginting, Rosdanelli Hasibuan (Universitas Sumatera Utara, 2014)
Bioplastics are a type of plastic made ​​from renewable biomass sources, such as vegetable oil, corn starch, pea starch, and microbiota. Starch from tubers of talas (Colocasia esculenta) as a potential raw material for bioplastics by using glycerol as plastizicer. The purposes of the research are to know effect of adding glycerol to the properties of tensile strength and elongation at break bioplastic from starch taro tubers. In this research, the manufacture of bioplastics using casting methode with variations of starch solution (0,2 w/v, 0,3 w/v, and 0,4 w/v). The next additions to vary the volume of glycerol (1 % v, 2 % v, and 3 % v) and heating temperature of gelatin formation (60oC, 70oC, and 80oC). The results showed that bioplastics made ​​from taro tuber starch has gelatinization temperature of 70oC. The addition of glycerol volume effect value of tensile strength and elongation at break of bioplastics. Increasing volume of glycerol will decrease tensile strength but increase elongation at break value. The best of bioplastics in this research is a variation of starch bioplastic 0,3 w/v, addition of 1 % v glycerol at a temperature of 70°C with a value of tensile strength is 18,4992 MPa and elongation at break value is 2,1290%.